Analysis of Student’s Mathematical Communication Skills through Problem Based Learning Models Assisted by Augmented Reality - Batubara, Ismail Hanif; Saragih, Sahat; Simamora, Elmanani; Napitupulu, E. Elvis; Sari, Indah Purnama (Budapest International Research and Critics University, 2022)
This study aims to determine whether the increase in mathematical communication skills of students who received the Problem Based Learning Learning Model based on Augmented Reality was higher than the increase in mathematical communication skills of students who did not receive a problem-based learning model. Students' mathematical communication skills measured in this study include students' abilities in terms of modeling, namely:Presenting real objects, pictures, or diagrams into mathematical ideas, Drawing is Expressing mathematical ideas orally or in writing in the form of images or visuals and Reporting, namely Using language, notation and mathematical structures to present and communicate ideas to draw conclusions. This research is a quasi-experimental study with a population of all students of SMP Muhammadiyah 04 Medan Indonesia. Two classes are selected at random from the available classes. The experimental class was treated with a culture-based Problem Based Learning learning model with Augmented Reality assistance, while the control class was not given any treatment. Data analysis was carried out using parametric statistics, namely the t-test. The results showed that the increase in students' mathematical communication skills who were taught through the culture-based Problem Based Learning learning model assisted by Augmented Reality was higher than the increase in the mathematical communication skills of students who were not given the Augmented Reality-assisted culture-based Problem Based Learning learning.